Navigating the Starlink Era of Personal Data Protection in Indonesia - Nudan, Pankrasius Wahu; Widodo, Pujo; Affifudin, M. (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the digital era, satellite technology such as Starlink by SpaceX offers high-speed broadband internet, but raises concerns regarding the privacy of users' personal data. This research aims to analyze the impact of using Starlink on data privacy in Indonesia, assess the readiness of technological infrastructure and data protection policies, and compare Indonesia's policies with other countries. Human rights theory, personal data protection theory, interactive justice theory, and governed interdependence theory were used to understand this context. The results show that the use of Starlink affects the privacy of users' personal data through data collection without consent, the risk of insecure data storage, and unauthorized access by third parties. Indonesia has several laws such as the ITE Law and the Personal Data Protection Law, but their implementation and enforcement need to be improved. Comparison with other countries such as the European Union which has GDPR shows the need for more comprehensive regulations in Indonesia. This research recommends increased awareness about data privacy, adoption of stringent data security practices, and development of comprehensive regulations. In conclusion, it is important for Indonesia to develop a personal data protection strategy that is balanced with satellite technology innovation to maintain individual privacy in the digital era.